UJI KEMAMPUAN BAKTERI TERMOFIL KOMPOS DALAM MENGURAIKAN POLY(3-HYDROXYBUTYRATE) DAN KOPOLIMERNYA DENGAN MENGGUNAKAN METODE POLYMER OVERLAY - Sri Wahyono (Jurnal Teknologi Lingkungan, 2004)
The primary aim of this project were to isolate the termophilic bateria from compost and to test their capability in degrading of Poly(3-hydroxybutyrate) and its copolymer (P(HB-co-5%HV), P(HB-co-8%HV), P(HB-co-12%HV)) using of polymer overlay methode. Testing of their capability was done in pH 8,0 and temperature of 55oC and 60oC. Fifteen isolates of thermophilic bacteria have been isolated and can be classified into 4 groups based on the profile of their growth rate, clear zone formation, and capability of PHB degradation. In the incubation of 55oC, degradation rate of Poly(3-hydroxybutyrate) was generally slower than their copolymer.